Influence of purple basil extract (Ocimum basilicum L.) on chemical composition, rheology and antioxidant activity of set-type yoghurt - Gurkan, Hacer (Array, 2019)
Four different types of yoghurt were manufactured using purple basil which was added to milk as water extract or powder forms at levels of 1.0 % and 0.4 % (w/w). Physicochemical and rheological properties, antioxidant capacity, color and total phenolic contents of yoghurt samples were measured during 21 days of storage. None of changes were observed for titratable acidity, pH and hardness parameters of yoghurt samples; however, some changes were observed during storage. The contents for total phenolic compounds and antioxidant activity [2,2'-Azino-bis(3-ethylbenzothiazoline-6-sulfonic acid diammonium salt (ABTS+*) and 2,2-Diphenyl-1-picrylhydrazyl (DPPH*) values] were dramatically higher in powder-added yoghurt samples than those of its water extract counterparts, while the lowest total phenolics and ABTS+* were observed in control sample during storage. The values for storage and loss modulus were higher in water extract-added samples than powder-added counterparts. In conclusion, no significant effect of the addition of powder or water extract of basil was observed on gross chemical characteristics of yoghurt, while use of basil powder positively contributed to antioxidant activity and changed the rheological behavior of yoghurt gel.